PREPARATION AND EVALUATION OF HERBOMINERAL FORMULATION - SEPTIPAT 250 TABLET (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is the oldest system of medicine. Ayurvedic, herbal and herbo-mineral preparations are used for the treatment of chronic and degenerative diseases with less side-effects. Septipat - 250 Tablet is a compound herbomineral formulation widely used in Ayurvedic clinical practice as natural antibiotics, which has a tendency to kill the bacteria and give health and hygiene. Septipat - 250 Tablet consists of Kanchnar (Bauhinia variegata), Gulvel (Tinospora cordifolia), Shuddha Guggul (Commiphora mukul), Nagakaeshar (Mesua ferrea) and four mineral ingredients Tamra bhasma, Mandur bhasma, Shadgun Kajjali and Saindhav Lavana. The detailed evaluation of this Patented and Properitory Product was studied for the following parameters: physico-chemical, elemental assay and HPLC analysis of the product. The parameters were found to be sufficient and set as reference specification for the Septipat - 250 Tablet quality control study.